Globalization of U.S. small technology firms : a practitioner perspective on selected electronics-related sectors / John S. Bowers and Ilan Alon - S. Bowers, John; Alon, Ilan (Faculty of Business and Management ; UiTM Press, 2000)
This paper reviews various factors that owners and managers of U. S. small technology firms in the aircraft & spacecraft, electrical machinery, and instrument industries can consider as they become more involved with the internationalization of their businesses. Small businesses, including small technology firms, are an important aspect of each country's economy. As a result of globalization, these types of small businesses can grow and improve profitability by taking advantage of business opportunities in various countries and regions throughout the world. International trade for three industries aircraft & spacecraft, electrical machinery, and instruments) is reviewed to illustrate the potential opportunities for small technology firms in these industries.